RENCANA PENATAAN KAWASAN TRANSIT WATERWAY (TRANSPORTASI AIR) SUNGAI CISADANE KOTA TANGERANG - Muhamad Ichsan Zafiri; Suryono Herlambang; Parino Rahardjo (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Tangerang City plans to develop water transportation in the context of providing transportation modes other than land transportation, the transportation development plan is the development of water transportation by utilizing the cisadane river as its route, one of the docks planned namely the dock of the great al-ijtihad mosque located in the center of Tangerang City and close to the Tangerang KRL Station, so there is potential for the proximity of the two modes of transportation. The purpose of this research is to determine the feasibility and carrying capacity of the cisadane river to be utilized in the development of water transportation and to determine the need for infrastructure and facilities needed to integrate the water transportation wharf plan of the grand mosque of Al- ijtihad cisadane river with Tangerang KRL station.. This type of research is qualitative and quantitative research using descriptive analysis methods in the overall analysis of the analysis. Then from all the analyzes that have been carried out, it is obtained the direction of the structuring plan which broadly includes the provision of open space, widening pedestrian, recommendations for moving out / entering the Tangerang KRL station and the results are in the form of a regional site plan which is planned to contain elements of the provision of facilities, infrastructure and facilities in the vicinity of the water transportation transit area and arrangement in accordance with the direction of intermodal area integration. Keywords: intermoda integration; railway station; transit area planning; water transportation AbstrakKota Tangerang berencana melakukan pengembangan transportasi air dalam rangka menyediakan pilihan moda transportasi selain transportasi darat, rencana pengembangan transportasi tersebut adalah pengembangan transportasi air dengan memanfaatkan sungai cisadane sebagai jalurnya, salah satu rencana titik dermaga yakni dermaga masjid agung al-ijtihad berada di pusat Kota Tangerang dan berada dekat dengan Stasiun KRL Tangerang, sehingga adanya potensi dari dekatnya letak kedua moda transportasi tersebut. Tujuan dari penelitian ini adalah untuk mengetahui kelayakan dan daya dukung sungai cisadane untuk dimanfaatkan dalam pengembangan transportasi air dan mengetahui kebutuhan sarana, prasarana dan fasilitas yang dibutuhkan untuk mengintegrasikan rencana dermaga transportasi air masjid agung al-ijtihad sungai cisadane dengan stasiun KRL Tangerang. Jenis penelitian ini merupakan penelitian kualitatif dan kuantitatif dengan menggunakan metode analisis deskriptif dalam pembahasan keseluruhan analisisnya. Kemudian dari seluruh analisis yang telah dilakukan, didapatkanlah arahan rencana penataan yang secara garis besar meliputi penyediaan ruang terbuka, pelebaran pedestrian, rekomendasi pemindahan akses keluar/masuk stasiun KRL Tangerang yang kemudian hasilnya berupa usulan rencana siteplan kawasan yang didalam rencananya terdapat unsur penyediaan kebutuhan sarana, prasarana dan fasilitas pada sekitar kawasan transit transportasi air dan penataan yang sesuai dengan arahan integrasi kawasan antarmoda.